2020
DOI: 10.1186/s12888-020-02673-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of social support and emotional exhaustion in the association between work-family conflict and anxiety symptoms among female medical staff: a moderated mediation model

Abstract: Background: Limited work has been done to explain how work-family conflict is related to anxiety symptoms and the roles of emotional exhaustion and social support may play. Methods: Based on a sample of 764 female nurses and physicians, a model was tested in which emotional exhaustion served as a mediator and social support was regarded as a moderator between work-family conflict and anxiety symptoms. Results: This current study supported a moderated mediation model where the relationship between work-family c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 51 publications
3
47
0
4
Order By: Relevance
“…In this study, medical staff's anxiety may be mainly manifested as worries regarding the risk of infection when treating patients with suspected COVID-19 pneumonia. Social support had been proven to buffer the effect of perceived stress on anxiety [e.g., ( 59 , 60 )]. Yet, medical staff are likely to be away from family during this period, which could mitigate the possible role of family as sources of hope; similarly, as one's medical staff peers are also under stress, they may not be potent hope sources, too.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, medical staff's anxiety may be mainly manifested as worries regarding the risk of infection when treating patients with suspected COVID-19 pneumonia. Social support had been proven to buffer the effect of perceived stress on anxiety [e.g., ( 59 , 60 )]. Yet, medical staff are likely to be away from family during this period, which could mitigate the possible role of family as sources of hope; similarly, as one's medical staff peers are also under stress, they may not be potent hope sources, too.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is a debate among researchers on the exact relationship between burnout and depression as some scholars regard burnout as a depression dimension [ 49 ] while others consider the two as different constructs [ 48 ]. With respect to the burnout–anxiety relationship, although less commonly investigated, these two psychological phenomena show strong and positive associations [ 50 , 51 ]. However, in a recent meta-analysis it was shown that burnout is differentiated from both depression and anxiety as studies that observe significant associations show mainly medium effect sizes while the tools being used to measure for these three phenomena also appear to affect the observed associations [ 48 ].…”
Section: Burnout Depression Anxiety and Cognitive Functioningmentioning
confidence: 99%
“…Dukungan sosial secara signifikan dapat mengurangi efek merugikan dari kondisi stres untuk mencegah masalah mental bagi individu. Sebuah literatur menunjukkan bahwa dukungan sosial dikaitkan secara negatif dengan tekanan psikologis (Zhang et al, 2020).…”
Section: Pendahuluanunclassified